In-vitro dissolution of compressed tamarind and pineapple powder tablets - Mokhtar, Taufiq Aminullah; Yusof, Yus Aniza; Chin, Nyuk Ling; Othman, Siti Hajar; Serikbayeva, Asya Demeukhanovna; Aziz, Mohammad Gulzarul (Elsevier, 2014)

(untitled)
Tamarind and pineapple fruit powders dissolution properties are important as it depends on time taken for it to dissolve. Both powders produced from spray drying with addition of 10% w/v of maltodextrin. The tamarind and pineapple fruit powders were then compressed into tablets with applied force of 28.65 MPa. A dissolution tester was used for in-vitro dissolution studies. These findings indicate the moisture content, bulk density, tapped density and water activity showed a significant difference at P < 0.05. Thus, it is important to compress fruit powder into tablet form as it easy to dissolve and provide healthy beverages to meet consumer's demand.